A dual positional specific lipoxygenase functions in the generation of flavor compounds during climacteric ripening of apple. (25th February 2015) - Schiller, Doreen; Contreras, Carolina; Vogt, Jörg; Dunemann, Frank; Defilippi, Bruno G; Beaudry, Randolph; Schwab, Wilfried
Abstract: Lipoxygenase (LOX) is an important contributor to the formation of aroma-active C6 aldehydes in apple ( Malus × domestica ) fruit upon tissue disruption but little is known about its role in autonomously produced aroma volatiles from intact tissue. We explored the expression of 22 putative LOX genes in apple throughout ripening, but only six LOXs were expressed in a ripening-dependent manner. Recombinant LOX1:Md:1a, LOX1:Md:1c, LOX2:Md:2a and LOX2:Md:2b proteins showed 13/9-LOX, 9-LOX, 13/9-LOX and 13-LOX activity with linoleic acid, respectively. While products of LOX1:Md:1c and LOX2:Md:2b were S-configured, LOX1:Md:1a and LOX2:Md:2a formed 13(R)-hydroperoxides as major products. Site-directed mutagenesis of Gly567 to an alanine converted the dual positional specific LOX1:Md:1a to an enzyme with a high specificity for 9(S)-hydroperoxide formation. The high expression level of the corresponding MdLOX1a gene in stored apple fruit, the genetic association with a quantitative trait locus for fruit ester and the remarkable agreement in regio- and stereoselectivity of the LOX1:Md:1a reaction with the overall LOX activity found in mature apple fruits, suggest a major physiological function of LOX1:Md:1a during climacteric ripening of apples. While LOX1:Md:1c, LOX2:Md:2a and LOX2:Md:2b may contribute to aldehyde production in immature fruit upon cell disruption our results furnish additional evidence that LOX1:Md:1a probably regulates the availability of precursors for ester production in intact fruit tissue. Abstract : Fruit crops: Achieving that apple aroma Scientists studying enzymes called lipoxygenases have identified a key player in generating the aroma of ripe apples. Until now, little was known about the biochemical pathways producing the volatile compounds that give apples their smell. In one such pathway, lipoxygenase (LOX) enzymes break down fatty acids into alcohols. These are converted into molecules called esters, which comprise up to 80 per cent of the volatile compounds in apples. In a biochemical and genetic study of 22 LOX enxymes, Wilfried Schwab, of the Technische Universität München, Germany, and colleagues, found six were correlated with ripening. One of these, LOX1:Md:1a, is highly concentrated in stored apples, and its activity closely tracks the total LOX activity of mature fruits. The researchers conclude that LOX1:Md:1a plays a major role in producing ester precursors—and therefore aroma— in post-harvest apples.[135]